The Willing Suspension of Disbelief: Memoirs of an Abused Altar Boy. - WEST, PETER (Quadrant Magazine, 2019)
The article offers the author's thoughts about the common law concerning child sexual abuse cases involving the Catholic Church. Focus is given to the sensational testimony given by Gordon Hill concerning the sexual abuses he suffered at the hands of priests and nuns while he lived at a children's home, noting the inconsistencies and contradictions to the testimonies.